2018
DOI: 10.1039/c8ra00977e
|View full text |Cite
|
Sign up to set email alerts
|

Graphene oxide–metal oxide nanocomposites: fabrication, characterization and removal of cationic rhodamine B dye

Abstract: The fabrication and characterization of graphene oxide–iron oxide and graphene oxide–iron oxide–zirconium oxide nanocomposites have been reported. The decomposition of cationic rhodamine B dye by both nanocomposites has been examined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(33 citation statements)
references
References 68 publications
(69 reference statements)
0
29
0
Order By: Relevance
“…A modi-ed Hummers and Offeman's method was used to fabricate the GP nanosheet from natural graphite powder. 47,48 8 g of graphite powder (Sigma-Aldrich) and a stoichiometric amount of NH 4 NO 3 were added to 368 ml of 98% (w/w) H 2 SO 4 in an ice bath. KMnO 4 was slowly added to the mixture with continuous stirring until the solution turned green.…”
Section: Chemicals and Materialsmentioning
confidence: 99%
“…A modi-ed Hummers and Offeman's method was used to fabricate the GP nanosheet from natural graphite powder. 47,48 8 g of graphite powder (Sigma-Aldrich) and a stoichiometric amount of NH 4 NO 3 were added to 368 ml of 98% (w/w) H 2 SO 4 in an ice bath. KMnO 4 was slowly added to the mixture with continuous stirring until the solution turned green.…”
Section: Chemicals and Materialsmentioning
confidence: 99%
“…It was observed that newly fabricated GO-Fe 3 O 4 (3.66 eV) and GO-Fe 3 O 4 @ZrO 2 (3.20 eV) nanocomposites have the advantage of smaller bandgaps than GO (4.00 eV), which result in increased adsorption capacity and photocatalytic effects. Results confirmed that RhB is efficiently adsorbed over the surface of graphene oxide (~93%) and has a significant inhibitory effect against E. coli bacteria [51].…”
Section: Photocatalytic Degradation Of Dyesmentioning
confidence: 65%
“…In the recent years, GO‐Fe 3 O 4 magnetic catalyst has shown interesting potential in catalysis because of their high dispersion, high reactivity, and magnetic capability for easy phase separation and also showed antibacterial activity against Escherichia coli . [ 185 ]…”
Section: Go‐supported Metal Oxides As Catalystmentioning
confidence: 99%